GAYA KEPEMIMPINAN YANG EFEKTIF DALAM UPAYA MENINGKATKAN KINERJA KARYAWAN PADA PT. SUMBER MAS INDAH PLYWOOD - AMBARWATI, NIA (Jurnal Akuntansi AKUNESA, 2015)
AbstractThis research aims to analyze and explain a style of leadership that is applied in PT. Sumber Mas Indah Plywood and problems arising from the applied leadership style. and then determine the leadership style that is effective in improving the performance of employees at PT. Sumber Mas Indah Plywood. This research use the draft or a descriptive qualitative research design and data analysis in this study uses descriptive analysis of narrative. The result show that PT. Sumber Mas Indah Plywood tends to be used Exsploitive autoritative leadership style, while employees want to be consultative and partisipative leadership style.Keywords: Leaderhip Style, Employee Performance